The main changes in the new version of the ISO 9001 standard in comparison with the current version of 2008 for enterprise management; Молодежь и современные информационные технологии; Т. 2 - Durova T. S. (Информационные технологии в производстве и управлении, 2016)
Заглавие с титульного экрана